2017
DOI: 10.1007/s40429-017-0131-5
|View full text |Cite
|
Sign up to set email alerts
|

What Is Trained During Food Go/No-Go Training? A Review Focusing on Mechanisms and a Research Agenda

Abstract: Purpose of ReviewDuring food go/no-go training, people consistently withhold responses toward no-go food items. We discuss how food go/no-go training may change people’s behavior toward no-go food items by comparing three accounts: (a) the training strengthens ‘top-down’ inhibitory control over food-related responses, (b) the training creates automatic ‘bottom-up’ associations between no-go food items and stopping responses, and (c) the training leads to devaluation of no-go food items.Recent FindingsGo/no-go … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 57 publications
5
139
2
Order By: Relevance
“…Instead, many studies have reported the change in inhibitory control accuracy (commission errors) over the course of training as supporting evidence for this first account (Jones, Hardman, Lawrence, & Field, 2017;Veling, Lawrence, Chen, Van Koningsbruggen, & Holland, 2017). Yet, improvements in inhibitory control accuracy over multiple training sessions could result from learning stimulus-stop contingencies instead of the strengthening of top-down control (Verbruggen, Best, Bowditch, Stevens, & McLaren, 2014;Veling et al, 2017). This alternative bottom-up account hypothesizes that No-Go stimuli trigger inhibition in a stimulus driven way, creating an automatic 'learned reflex' .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, many studies have reported the change in inhibitory control accuracy (commission errors) over the course of training as supporting evidence for this first account (Jones, Hardman, Lawrence, & Field, 2017;Veling, Lawrence, Chen, Van Koningsbruggen, & Holland, 2017). Yet, improvements in inhibitory control accuracy over multiple training sessions could result from learning stimulus-stop contingencies instead of the strengthening of top-down control (Verbruggen, Best, Bowditch, Stevens, & McLaren, 2014;Veling et al, 2017). This alternative bottom-up account hypothesizes that No-Go stimuli trigger inhibition in a stimulus driven way, creating an automatic 'learned reflex' .…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption has only been tested once by including inhibitory control as an outcome measure with a pre-test/ post-test design, with no effects of GNG training on top-down inhibitory control (Adams et al, 2017). Instead, many studies have reported the change in inhibitory control accuracy (commission errors) over the course of training as supporting evidence for this first account (Jones, Hardman, Lawrence, & Field, 2017;Veling, Lawrence, Chen, Van Koningsbruggen, & Holland, 2017). Yet, improvements in inhibitory control accuracy over multiple training sessions could result from learning stimulus-stop contingencies instead of the strengthening of top-down control (Verbruggen, Best, Bowditch, Stevens, & McLaren, 2014;Veling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Others have hypothesized and demonstrated that instead (or additionally), repeatedly inhibiting responses to highly evaluated stimuli leads to devaluation of those stimuli. Since the stimuli are liked less after training, they should also be easier to resist outside the laboratory (Jones et al, 2016;Veling, Lawrence, Chen, van Koningsbruggen, & Holland, 2017). However, only few studies have investigated changes in implicit attitudes toward trained food items as a mechanism of Go/No-Go training (Aulbach et al, 2019;Houben & Jansen, 2015;Kakoschke, Kemps, & Tiggemann, 2017;Verbeken, Braet, Naets, Houben, & Boendermaker, 2018).…”
mentioning
confidence: 99%
“…A behavioural intervention that trained no-go r e s p o n d i n g t o h i g h -c a l o r i e f o o d c u e s l e d t o devaluation of those items in normal-weight [184,185] and in morbidly obese participants [34,186], as well as impulsive food choices in normal-weight individuals [184,185]. The authors have proposed that training acts bottom-up by creating associations between no-go food items and stopping responses and reducing valuation of no-go food items (in the affective loop) [187]. A similar mechanism may explain a reduction of food intake in uncontrolled eaters after inhibitory control training [82] and of approach bias to unhealthy food cues in obesity after training automated action tendencies [42,188].…”
Section: Behavioural Control and Action Inhibitionmentioning
confidence: 99%